MOTIVASI BELAJAR DITINJAU DARI DUKUNGAN KELUARGA DAN SCHOOL WELL-BEING - Nur Ainy Sadijah (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2021)
The role of the family has the influence to overcome all obstacles both from internal and external students in realizing all the ideals and hopes. Family support can increase learning motivation, sense of security and attention of students who are still in school. The form of family expression through empathy and acceptance helps students with enthusiasm to manifest individual enthusiasm in the learning process. High learning motivation is also caused by school well-being which is used by school institutions to understand all the basic needs for students and hope that individuals feel satisfaction, well-being and comfort in school with all the processes so as to reduce low learning motivation, this makes students feel prosperous, happy, happy in studying at school. This study aims to determine the effect of family support and school well-being on learning motivation in students of SMP Negeri 1 Telukjambe Timur Karawang. The number of samples used was 205 students of SMP Negeri 1 grades 7 and 8 East Telukjambe using probability sampling method. Based on the multiple regression analysis test that there is an influence between family support and school well-being on the learning motivation of students of SMP Negeri 1 Telukjambe Timur Karawang grades 7 and 8 with a Sign value. 0.000 <0.005, which means that family support and school well-being affect students' learning motivation by 23.1%. Keywords: Learning motivation, family support, school well-being Peran keluarga memiliki pengaruh untuk mengatasi segala rintangan baik dari internal maupun ekternal siswa dalam mewujudkan semua cita-cita dan harapan. Dukungan keluarga mampu meningkatkan motivasi belajar, rasa aman dan perhatian siswa yang masih duduk dibangku sekolah. Bentuk ungkapan keluarga melalui empati dan penerimaan membantu siswa dengan semangat untuk mewujudkan semangat individu dalam proses belajarnya. Motivasi belajar yang tinggi juga di sebabkan oleh school well-being yang, dijadikan oleh institusi sekolah untuk memahami segala kebutuhan mendasar bagi siswa dan berharap individu merasakan kepuasan, kesejahteraan dan kenyamanan di sekolah dengan segala prosesnya sehingga mengurangi rendahnya motivasi belajar hal ini membuat siswa merasa sejahtera, senang, bahagia di dalam menuntut ilmu di sekolah. penelitian ini bertujuan untuk mengetahui pengaruh dukungan keluarga dan school well-being terhadap motivasi belajar pada siswa SMP Negeri 1 Telukjambe Timur Karawang. Jumlah sampel yang digunakan 205 siswa SMP Negeri 1 kelas 7 dan 8 Telukjambe Timur dengan menggunakan metode probability sampling. Berdasarkan uji analisis regresi berganda bahwa terdapat pengaruh antara dukungan keluarga dan school well-being terhadap motivasi belajar siswa SMP Negeri 1 Telukjambe Timur Karawang kelas 7 dan 8 dengan nilai Sign. 0,000 < 0,005 yang artinya dukungan keluarga dan school well-being mempengaruhi motivasi belajar siswa sebesar 23.1%. Kata Kunci: Motivasi belajar, dukungan keluarga, school well-being